Health‐care use and cost in dementia caregivers: Longitudinal results from the Predictors Caregiver Study. Issue 4 (17th March 2014) - Zhu, Carolyn W.; Scarmeas, Nikolaos; Ornstein, Katherine; Albert, Marilyn; Brandt, Jason; Blacker, Deborah; Sano, Mary; Stern, Yaakov
Abstract : Objective: To examine the effects of caregiver and patient characteristics on caregivers' medical care use and cost. Methods: One hundred forty‐seven caregiver/patient dyads were followed annually for 6 years in three academic Alzheimer's disease centers in the United States. Logistic, negative binomial, and generalized linear mixed models were used to examine overall effects of caregiver/patient characteristics on caregivers' hospitalizations, doctor visits, outpatient tests and procedures, and prescription and over‐the‐counter medications. Results: Patients' comorbid conditions and dependence were associated with increased health‐care use and costs of caregivers. Increases in caregiver depressive symptoms are associated with increases in multiple domains of caregivers' health‐care use and costs. Discussion: Findings suggest expanding our focus on dementia patients to include family caregivers to obtain a fuller picture of effects of caregiving. Primary care providers should integrate caregivers' needs in health‐care planning and delivery. Clinical interventions that treat patients and caregivers as a whole will likely achieve the greatest beneficial effects.